PENGARUH PENERAPAN APLIKASI “BIDANKU” TERHADAP PENINGKATAN PENGETAHUAN DAN EFIKASI DIRI IBU NIFAS - Farhati Farhati; Yulia Ulfah Fatimah; Chris Sriyanti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
The postpartum period is a critical period for the mother, approximately 60% of maternal deaths occur after delivery, and 50% of postpartum deaths occur within the first 24 hours of labour. This period is an important transitional period, but in women's health care, it is an aspect that is often neglected. Preparations for the puerperium that have not been given since pregnancy have caused mothers not to know how to properly care for themselves and their babies. One of the bridges to optimize postnatal education efforts is through the development of the "BIDANKU" application which contains information and care management that can be used as a guide for postpartum mothers so that they can live the postpartum period in a healthy, safe, and prosperous manner. This study aimed to analyze the effect of applying the application "Bidanku" on increasing the knowledge and self-efficacy of postpartum mothers. This research was a quasi-experimental pre-post test design with control groups conducted in the city of Bandung with 60 samples of postpartum mothers as subjects. The analysis used a numerical categorical comparative test. The results showed that there were significant differences in the knowledge and self-efficacy of postpartum mothers between the control and treatment groups with a p<0.05. The application of the "Bidanku" application plays a role in increasing the knowledge and self-efficacy of postpartum mothers. The "Bidanku" application can be used as an alternative educational medium in midwifery care for postpartum mothers.